Remaking the human : cosmetic technologies of body repair, reshaping, and replacement - Jarrín, Alvaro, 1980-; Pussetti, Chiara (Politics of repair, 2021)
"The technological capacity to transform biology - repairing, reshaping and replacing body parts, chemicals and functions - is now part of our lives. Humanity is confronted with a variety of affordable and non-invasive 'enhancement technologies': anti-ageing medicine, aesthetic surgery, cognitive and sexual enhancers, lifestyle drugs, prosthetics and hormone supplements. This collection focuses on why people find these practices so seductive and provides ethnographic insights into people's motives and aspirations as they embrace or reject enhancement technologies, which are closely entangled with negotiations over gender, class, age, nationality and ethnicity"--